Effect of organic soil amendments on growth and phytochemical content of Sabah Snake Grass (Clinacanthus Nutans) - Wong, Kean Hoe (2016)
Clinacanthus nutans is one of the traditional herbs, which is famous for its multiple medicinal usages and well known for its antioxidant ability. The objective of this study was to study the effect of organic soil amendments in enhancing the growth and phytochemical contents of C nutans. These organic soil amendments were on-farm resources, such as Empty Fruit Bunch (EFB), Spent Mushroom Substrate (SMS), Rice Husk Biochar and Rice Bran. Topsoil was used as control medium in this study while all the soil organic amendments were applied in topsoil medium in ratio of 1:20 wt/wt (100g organic soil amendment with 2000g topsoil). After 13 weeks of planting, it was found that rice bran treatment enhanced the most in C nutans growth development (plant height, leaf and branch number, leaf width and leaf dry matter content) followed by rice husk, EFB, SMS and control treatment. Extract of C nutans treated with rice bran also showed the highest reducing power in DPPH scavenging activity, followed by EFB and SMS treatment. Meanwhile, C nutans treated with EFB reported highest total phenolic content among all treatments. However, the total flavonoid content between control and organic soil amendment has no significant different. This study concluded that rice bran treatment is the best treatment in promoting growth, yield and antioxidant activity of C nutans. While EFB treatment is the most ideal treatment for enhancing total phenolic content in C nutans. All data were analyzed statically by using one-way ANOVA test with 5% significant level.